Rain dance to research - Donnan, John A.; Donnan, Marcia (New York : D. McKay Co., 1977)
Discusses the history of man's efforts to control the weather from the methods of the earliest "weather makers" to the most sophisticated methods used today.
Includes index.
Keywords: Weather control -- History -- Juvenile literature; Rain-making -- History -- Juvenile literature; Weather control -- History